Spirituality and psychology: Converging themes - Ferreira , Halana Alves Quinta; Hasan, Shadia; Lopes, Stella Maris Brum (Seven Editora, 2024)
The theme of spirituality as an object of study and as a component of human life was recognized as relevant to health, be it physical and/or mental. Even though it is a relevant topic, there is a gap in the knowledge of the spirituality of psychology professionals in Brazil and its impact on research and clinical practice. This research aims to analyze the scientific productions about psychology and its relationship with the themes of spirituality. This is a qualitative research through the integrative literature review, the search was carried out on the Portal of Periodicals (CAPES) and the Brazilian Digital Library of Theses and Dissertations (BDTD) using the descriptors spirituality, psychology and psychological practices, where 9 works were selected, including theses and dissertations, published between the periods of 2012 to 2020. The results were classified according to: objective, methodology and results. Three themes were identified: religiosity and spirituality; professional training and clinical practice. Of the works analyzed, there were 3 theses and 6 dissertations and in relation to the methodology, the two quantitative researches present surveys carried out with psychologists, two works were conducted within specific theoretical approaches: Brazilian gestalt-therapists and cognitive-behavioral therapy. Qualitative research was carried out through interviews with 24 clinical psychologists and 2 students in the process of training. Two studies were integrative reviews and one literature review of national and international articles and TCCs. Regarding the objectives of the research analyzed, the general objectives are related to religiosity and spirituality in the context of clinical practices. The understanding of the concepts of religiosity, spirituality and psychology is the focus of 04 works. The theoretical currents that underlie the research are linked to the objectives of three works, being respectively Gestalt, Cognitive-Behavioral Therapy, Logotherapy/existential psychology, and Analytical Psychology. Psychologists' personal perspective on the topic and its repercussions are addressed in a thesis, while the patients' perspective is explored in a dissertation. It is concluded that it is essential for psychology professionals to take an individualized approach when dealing with spiritual issues. Everyone has their own beliefs and values in this regard, and it is important to respect and consider them during the therapeutic process. DOI:https://doi.org/10.56238/sevened2024.010-033